2022
DOI: 10.1002/vetr.1267
|View full text |Cite
|
Sign up to set email alerts
|

Preventive hoof trimming in dairy cattle: Determining current practices and identifying future research areas

Abstract: Background:The extent to which preventive hoof trimming is implemented on Great Britain's (GB) dairy farms is unknown. The aims of this study were to determine common practices and capture producers' input on key areas that require further research. Methods: An online survey was conducted over a 4-week period from March to April 2017. Results: A total of 338 valid survey responses were received. The majority of farmers undertook preventive hoof trimming (82.4%), and this was significantly positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In a Great Britain´s study producers were surveyed about undertaking preventive hoof trimming. The study results suggest that preventive hoof trimming was associated with increased herd yield [ 26 ]. However, no data was available to quantify the economic impact of prevention as expert opinion could not provide more clarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Great Britain´s study producers were surveyed about undertaking preventive hoof trimming. The study results suggest that preventive hoof trimming was associated with increased herd yield [ 26 ]. However, no data was available to quantify the economic impact of prevention as expert opinion could not provide more clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Hoof trimming is a management strategy with both, preventive and therapeutic potential, for SU [ 25 , 26 ], with regular hoof trimming commonly recommended [ 8 ]. Two different hoof trimming strategies as a management practice in Alberta, Canada, were reported: 1. partial herd hoof trimming, where approximately 18% (±18.3) of the herd is trimmed every 2 months; 2. whole herd hoof trimming, with 6-month intervals between trims [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the young age group, an average minimum dorsal wall length of 7.5 and 8.2 cm if the claws were trimmed to a step or to a point, respectively was calculated. A study that investigated current practices of preventative claw trimming in UK dairy herds reported that only 5.9% of respondents reported preventative claw trimming in pre-calving heifers [21]. A randomized controlled trial that evaluated the effectiveness of routine foot trimming of heifers 3 weeks pre-calving and 100 days post-calving in reducing the rst lactation lameness and improving milk production reported that preventative trimming in heifers pre-or post-calving was not associated with lameness prevalence, time to rst lameness, 305-day lactation milk yield, or the type of lesions identi ed during dry-off claw trimming compared with only performing locomotion scoring [46].…”
Section: Discussionmentioning
confidence: 99%
“…Routine claw trimming has been established as a component of a lameness prevention plan for dairy cattle herds [17][18][19][20], with 82.4% of dairy farmers practicing routine trimming in the UK [21]. Functional claw trimming reduces the risk of lameness development by improving foot balance between the lateral and medial claws, increasing the contact area with the ground [22], resulting in improved grip [23], and reducing external weight from the typical sole ulcer site at the axial sole [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…2 Additionally, questions about when and how frequently to perform hoof trimming are common among farmers. 3 The hoof wall grows at a rate of approximately 7 mm per month, while the normal growth rate of the sole's horn is about 3 mm per month. 4 The rate of hoof wear depends on the animal's environment and daily walking distance.…”
Section: Right Animalmentioning
confidence: 99%